Correlation of muscle strength and reported knee function after Anterior Cruciate Ligament (ACL) graft, unrepaired ACL injury, and healthy knees (Research, Society and Development, 2024)
Introduction: Many tools can be used for functional assessment following an Anterior Cruciate Ligament (ACL) injury or reconstruction. These include the assessment of stability, the assessment of neuromuscular factors such as strength, and the patient's perception of knee function. The manual dynamometer (MD) is a strength assessment tool that can be used in environments where isokinetic assessment is not feasible. The Lyshom questionnaire, Tegner scale, and the International Knee Documentation Committee (IKDC) scale are validated instruments for subjective functional assessment. Objective: To evaluate the correlation between muscle strength and reported knee function after ACL grafting, unrepaired ACL injury, and healthy knees. Methods: 95 male subjects were evaluated, 36 with ACL reconstruction, 23 with unrepaired ACL injury, and 36 without knee injuries. All were evaluated with the Lysholm questionnaire, Tegner, and IKDC scales. Muscle strength was assessed with the MD, and the limb symmetry index (LSI) was used to correlate with the reported function. Results: The lowest scores on the Lysholm questionnaires and Tegner and IKDC scales occurred in subjects with unrepaired injuries, with significance between groups (p=0.000–0.001). The association involving the ISL with the Lysholm questionnaire and IKDC scale was observed in the ISL of 10% and 15% only for the extension (p